Ginsenoside Rb1 and compound K improve insulin signaling and inhibit ER stress-associated NLRP3 inflammasome activation in adipose tissue - Weijie Chen; Junlian Wang; Yong Luo; Tao Wang; Xiaochun Li; Aiyun Li; Jia Li; Kang Liu; Baolin Liu (Journal of Ginseng Research, 2016)
Background: This study was designed to investigate whether ginsenoside Rb1 (Rb1) and compound K (CK) ameliorated insulin resistance by suppressing endoplasmic reticulum (ER) stress-induced inflammation in adipose tissue. Methods: To induce ER stress, epididymal adipose tissue from mice or differentiated 3T3 adipocytes were exposed to high glucose. The effects of Rb1 and CK on reactive oxygen species production, ER stress, TXNIP/NLRP3 inflammasome activation, inflammation, insulin signaling activation, and glucose uptake were detected by western blot, emzyme-linked immunosorbent assay, or fluorometry. Results: Rb1 and CK suppressed ER stress by dephosphorylation of IRE1α and PERK, thereby reducing TXNIP-associated NLRP3 inflammasome activation in adipose tissue. As a result, Rb1 and CK inhibited IL-1β maturation and downstream inflammatory factor IL-6 secretion. Inflammatory molecules induced insulin resistance by upregulating phosphorylation of insulin receptor substrate-1 at serine residues and impairing insulin PI3K/Akt signaling, leading to decreased glucose uptake by adipocytes. Rb1 and CK reversed these changes by inhibiting ER stress-induced inflammation and ameliorating insulin resistance, thereby improving the insulin IRS-1/PI3K/Akt-signaling pathway in adipose tissue. Conclusion: Rb1 and CK inhibited inflammation and improved insulin signaling in adipose tissue by suppressing ER stress-associated NLRP3 inflammation activation. These findings offered novel insight into the mechanism by which Rb1 and CK ameliorate insulin resistance in adipose tissue.